Folklore Literacy Transformation for Generation Alpha through Digital-Mediated Storytelling in a Southeast Sulawesi Village - Hasdairta Laniampe; La Niampe; Bainudin; Irawati Tapasi (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2026)
Background: The lack of interest in reading and declining awareness of folklore preservation in the digital era present significant challenges to the sustainability of oral traditions in Anggoeya Village, Southeast Sulawesi. As digital natives, Generation Alpha requires a literacy approach that is both adaptive and innovative. Preliminary observations showed that 100% of children used smartphones daily but none were familiar with QR codes for education or could identify local folklore narratives. Purpose of the Study: This community service program aims to revitalize the interest of elementary school-aged children (Generation Alpha) in Southeast Sulawesi folklore through the Digital-Mediated Storytelling method. Methods: The approach involved interactive socialization, technology demonstrations using QR Code scanning, and implementation of physical reading habits through the 15-Minute Reading Habit method. Five curated local stories (Oheo, La Moelu, Legenda Gunung Mekongga, La Sirimbone, Wandiu-Diu) were digitized into multimedia formats accessible via QR codes. The program engaged 15 elementary school students. Results: Evaluation indicated significant improvement in digital literacy and cultural understanding. Approximately 80% of participants (12 children) were able to operate QR Code scanning techniques independently, and 86.7% (13 children) successfully identified the moral values within local narratives. The initiative successfully established a